Europe and Central Asia - Health insurance and competition - World Bank (World Bank, 2012)
Health financing systems in some Europe and Central Asia (ECA) countries are undergoing some major reforms. In parallel with the transition from central planning to develop market-based economies, countries in Central Europe have moved within a relatively short period of time from having health systems that were government managed and funded by taxes to single health insurance systems that are payroll-funded. The next chapter (chapter two) describes the insurance context in Austria, the Netherlands, Slovakia, and Switzerland. Chapter three examines risk selection in a multiple insurance system. Risk-adjusters and equalization schemes in different countries are discussed as well as the resulting incentives for insurance companies to develop cost containment strategies. Chapter four discusses whether and how insurers compete for providers, including the different forms of managed care contracts that have evolved under multiple insurance and the impact of such contracts on policy goals. Chapter five describes consumer choice in different health financing systems and whether consumers are exercising their choice to switch insurers and plans. Chapter six presents an overview of the different options for insurance reforms. The final chapter will identify the main lessons drawn from the preceding chapters and will present potential policy solutions for increasing the effectiveness of insurance systems, including the necessary regulatory framework to prevent adverse effects, purchasing, improved risk pooling, and monitoring and evaluation systems.